2020
DOI: 10.1101/2020.10.27.20219097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-infection in critically ill patients with COVID-19: An observational cohort study from England

Abstract: Objective: To describe the incidence and nature of co-infection in critically ill adults with COVID-19 infection in England. Methods: A retrospective cohort study of adults with COVID-19 admitted to seven intensive care units (ICUs) in England up to 18 May 2020, was performed. Patients with completed ICU stays were included. The proportion and type of organisms were determined at <48 and >48 hours following hospital admission, corresponding to community and hospital-acquired co-infections. Results: Of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
2
12
1
Order By: Relevance
“…Since complicating bacterial infections are infrequent in the early hospitalisation period of COVID-19, this recognised concern in relation to the use of tocilizumab would be lessened with earlier use. 20 On the basis of the ISARIC4C database, approximately 49% of hospitalised COVID-19 patients in the UK would meet our inclusion criteria and hence would benefit from tocilizumab (ISARIC4C Investigators, personal communication). Sarilumab, an alternative IL-6 antagonist, is available but evidence of its efficacy is inconclusive 15 , 21 , 22 and the results of the largest trial ( NCT04315298 ) are not yet published.…”
Section: Discussionmentioning
confidence: 99%
“…Since complicating bacterial infections are infrequent in the early hospitalisation period of COVID-19, this recognised concern in relation to the use of tocilizumab would be lessened with earlier use. 20 On the basis of the ISARIC4C database, approximately 49% of hospitalised COVID-19 patients in the UK would meet our inclusion criteria and hence would benefit from tocilizumab (ISARIC4C Investigators, personal communication). Sarilumab, an alternative IL-6 antagonist, is available but evidence of its efficacy is inconclusive 15 , 21 , 22 and the results of the largest trial ( NCT04315298 ) are not yet published.…”
Section: Discussionmentioning
confidence: 99%
“…Since complicating bacterial infections are infrequent in the early hospitalisation period of COVID-19, this recognised concern in relation to the use of tocilizumab would be lessened with earlier use. 22 Based upon the ISARIC4C database, approximately 49% of hospitalised COVID-19 patients in the UK would meet our inclusion criteria and hence would benefit from tocilizumab (personal communication, ISARIC4C Investigators). CRP was chosen as the biomarker for inflammation in this study since it is widely used and affordable worldwide, it is correlated with serum IL-6 levels, and early clinical studies of COVID-19 had reported it to be associated with severity and prognosis, with a value of >50 mg/L associated with severe disease and a level of around 75 mg/L distinguishing fatal from non-fatal cases.…”
Section: Discussionmentioning
confidence: 99%
“…Since complicating bacterial infections are infrequent in the early hospitalisation period of COVID-19, this recognised concern in relation to the use of tocilizumab would be lessened with earlier use. 22…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a case–control study revealed that patients with cobacterial infection had greater proportion of severe/critical disease at presentation than those without co-infection (80 vs 30%; p < 0.001) [ 5 ]. Most importantly, patients with a co-infection had a prolonged length of hospital stay with an average of 29 ± 6.7 days and carried a higher risk of death than those without co-infection (odds ratio [OR]: 2.84; 95% CI: 1.42–5.66) [ 4 ] as previously reported [ 5 , 6 ].…”
Section: Epidemiologymentioning
confidence: 69%